Papua New Guinea food price bulletin: January 2025 - International Food Policy Research Institute; Schmidt, Emily; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2025)
Download time series food price data, and build graphs and tables for over 20 different food crops at our food price database webpage: https://www.ifpri.org/project/fresh-food-price-analysis-papua-new-guinea/ Price trends: Quarterly comparisons (Q4 2024 vs. Q4 2023 and Q4 2022) Sweet potato prices in Q4 of 2024 were 20.4 percent higher in all markets compared to Q4 of 2023 (averaging 1.64 PGK/kg in Q4 of 2023, and 1.79 PGK/kg in 2024). However, sweet potato prices in Kokopo were 13 percent lower in 2024 (1.35 PGK/kg) compared to 2023 Q4 price (1.55/PGK/kg) Rice prices have increased slowly (but remained stable) since 2022. Compared to Q4 2023, rice prices in 2024 were 14 percent higher in Kokopo, Lae and Port Moresby. Vegetable prices, on average, in Q4 of 2024 were 23.6 lower in Goroka compared to Q4 of 2023. Compared to Q4 2022, the price of vegetables, on average, in 2024 were 22.1 percent lower in highland markets. Fruits saw mixed price movements between 2023 and 2024: lemon prices in Q4 2024 were 28.4 percent lower, on average, across all markets.